Numerical Simulation of Damage Processes in CCD Detectors Induced by Multi-Pulse Nanosecond Laser Irradiation - Weijing Zhou; Hao Chang; Zhilong Jian; Yingjie Ma; Xiaoyuan Quan; Chenyu Xiao (Sensors)
This paper presents a finite element simulation of thermal damage to a CCD caused by nanosecond multi-pulse laser exposure. The temperature changes in the CCD due to the laser pulses were simulated, and the time evolution of thermal damage was studied. The impacts of different laser parameters such as spot radius, pulse width, and repetition frequency on thermal damage were evaluated. The results indicated that the temperature of the CCD increased with each pulse due to cumulative effects, leading to thermal damage. A smaller laser spot size intensified the temperature rise, accelerating the rate at which different layers in the CCD exceeded the relative melting point of each material. In the case of nanosecond pulse width, variations in pulse width had minimal effects on CCD thermal damage when repetition frequency and average power density were constant. Lower repetition frequencies made it easier to cause melting damage to the CCD when pulse width and average power density were constant.